The new high-yield debt market : a handbook for portfolio managers and analysts - Fabozzi, Frank J.; Cheung, Rayner (New York : Harper Business, 1990)
The book offers the most authoritative analytical framework for high-yield debt investments, and is a guide to valuing, buying, selling, trading and investing in this sector of the debt market.
Includes bibliographical references and index.
occ 16/01/2019
Loans
Keywords: Bonds; Portfolio management